A Review on Kidney Stone Detection using ML and DL Techniques - Dr. Sheshang Degadwala,; Varsha Rathva, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Kidney stone detection is a critical healthcare challenge, as timely and accurate diagnosis can prevent complications. The motivation behind this review is the increasing prevalence of kidney stones and the need for more effective, non-invasive detection methods. Machine learning (ML) and deep learning (DL) techniques offer promising solutions, leveraging medical imaging data to enhance diagnostic accuracy. However, limitations such as high computational cost and reliance on large datasets hinder their full potential. The aim of this review is to analyze the latest advancements in kidney stone detection using ML and DL techniques. The objective is to compare existing methodologies, highlight their strengths and weaknesses, and suggest future research directions, particularly in integrating transfer learning and fine-tuning techniques to enhance performance.
Keywords: Kidney Stone Detection; Machine Learning; Deep Learning; Medical Imaging; Transfer Learning; Fine-Tuning; CT Scans